Effect of flow operation modes on removal of acetic acid from oil palm frond biomass hydrolysate using hollow fiber supported liquid membrane - Abdul Wahab Mohammad,; Che Ku M. Faizal,; Norlisa Harruddin,; Syed M. Saufi,; Vikneswary Rajendaren,
Acetic acid (AA) is considered an inhibitor in the oil palm frond (OPF) biomass hydrolysate solution. It can reduce the microorganism activity during sugar fermentation using OPF solution. In the current study, a hollow fiber supported liquid membrane (HFSLM) system using hybrid polyethersulfone-graphene membrane support and organic liquid membrane phase of 0.5 M tri-n-octyl amine carrier in a 2-ethyl-1-hexanol diluent was used to remove the AA. The liquid membrane impregnation time and the flow operation modes of the feed and strip phases in the HFSLM configuration were investigated. Mode I was operated with the feed phase flow inside the hollow fiber (HF) lumen and the stripping phase flow at the shell side. In mode II, the feed phase entered at the shell side and the stripping phase at the lumen of the HF support. The best liquid membrane impregnation time was 4 hours, exhibiting the highest AA removal efficiency of 80% compared to 1 and 24 hours of impregnation time. The removal efficiency of the AA was 80.1% and 42.4% using mode I and mode II, respectively, at 8 hours of the supported liquid membrane (SLM) running time. HFSLM was applied to remove AA from real OPF biomass hydrolysate. It was found that the AA concentration had reduced from 6.83 to 2.01 g/L after the SLM process. The SLM process did not affect the concentration of other components, especially sugar compounds in the OPF biomass hydrolysate.